2010
DOI: 10.1097/scs.0b013e3181f40393
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of Pseudoaneurysm of the Internal Maxillary Artery After Orthognathic Surgery

Abstract: In orthognathic surgery, Le Fort I osteotomy is one of the most often used methods for the correction of dental-facial deformities and is considered technically safe. However, this procedure may lead to diverse complications, including uncommon vascular complications. A clinical case is described of late development of pseudoaneurysm in one of the branches of the maxillary artery in a 20-year-old patient who had undergone Le Fort I osteotomy, bilateral sagittal osteotomy of mandibular branch, and mentoplasty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 29 publications
(58 reference statements)
1
58
0
Order By: Relevance
“…Therefore, every brisk postoperative epistaxis must be suspected to originate from a pseudoaneurysm, certainly if the interval between the surgery and the epistaxis is prolonged. AVELAR et al reported no massive bleeding from the oral cavity upon physical examination of the patients 13 . In the present cases in which no bleeding site was identified during re-exploration or arteriography, massive bleeding was observed through both the oral and the nasal cavities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, every brisk postoperative epistaxis must be suspected to originate from a pseudoaneurysm, certainly if the interval between the surgery and the epistaxis is prolonged. AVELAR et al reported no massive bleeding from the oral cavity upon physical examination of the patients 13 . In the present cases in which no bleeding site was identified during re-exploration or arteriography, massive bleeding was observed through both the oral and the nasal cavities.…”
Section: Discussionmentioning
confidence: 98%
“…The cases described in this report occurred within the first 14 postoperative days, as in most patients with this condition 11 . In a review of epistaxis due to pseudoaneurysm after Le Fort I osteotomy, AVELAR et al 13 . demonstrated that these pseudoaneurysms occur 3 days to 8 months after the osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgeries were performed with relative ease, leading to minimal bleeding, especially when preoperative embolization was performed. 16 In addition, the procedure offered a wide surgical exposure, with good access to voluminous tumors, including those with intracranial extension. We believe that the resection of the posterior wall of the maxillary sinus allows a direct access to the vascular pedicle of the JA, thus permitting to control the vascular pedicle and facilitating hemostasis and total removal of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…20 Life-threatening hemorrhage is a rare complication after Le Fort I osteotomy. [21][22][23] The vessel most commonly involved in false aneurysms following mandibular surgery is the IMA. 22 Facial artery pseudoaneurysms were also described following maxillofacial as well as dentistry procedures.…”
Section: Le Fort Osteotomymentioning
confidence: 99%